2014
DOI: 10.5762/kais.2014.15.4.2207
|View full text |Cite
|
Sign up to set email alerts
|

Relations of Self-assertiveness, Self-esteem, Depression and Abnormal Eating Attitudes among Female University Students with Weight Control Experience

Abstract: The purposes of this study were to investigate self-assertiveness, self-esteem, depression and abnormal eating attitudes among female university students with weight control experience and to identify the factors that influence abnormal eating attitudes. Data were collected through self reported structured questionnaire form 170 Korean female university students by convenient sampling methods form May 1 to June 30, 2013. A multiple linear regression showed that depression(β=0.20, p=.029) was identified as sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Most previously published studies found that personal factors that influenced disordered eating behavior in female college students included body image distortion, self‐esteem, BMI, weight control behaviors, assertiveness, and internalization of social values concerning appearance . The relatively few studies on this topic also report the influence of social factors such as social physique anxiety .…”
Section: Introductionmentioning
confidence: 99%
“…Most previously published studies found that personal factors that influenced disordered eating behavior in female college students included body image distortion, self‐esteem, BMI, weight control behaviors, assertiveness, and internalization of social values concerning appearance . The relatively few studies on this topic also report the influence of social factors such as social physique anxiety .…”
Section: Introductionmentioning
confidence: 99%